Coherence in ongoing varieties. The effect of mesosocial and small-scale variables on the use of the intermediate (standard/vernacular) variety in southern Spain. - Villena-Ponsoda, Juan Andrés; Vida-Castro, Matilde Ángeles; Molina-García, Álvaro (My University, 2019)
This paper addresses some questions regarding coherence within ongoing urban varieties, such as the one boosted by urban middle-class speakers from southern Spain since the fifties of the 20th century (Villena and Vida 2017, 2018). The main issues we focus on here are (1) whether covariation and coherence actually exist within a variety which has primarily emerged on the basis of correction and levelling of vernacular features, and (2) to what extent it is feasible to build a multivariate model able to depict interaction between the macrosocial, mesocial and small-scales variables underlying the speaker’s use of the new variety.
Keywords: Sociolingüística; Español - Dialectología - Andalucía; Sociolinguistics; Coherence; Southern Spanish; Koineization